Thermo-economic analysis of integrated gasification combined cycle co-generation system with carbon capture and integrated with absorption refrigeration system. (15th November 2021) - Muhammad, Adnan; Muhammad, Zaman; Ullah, Atta; Muhammad, Rizwan; Ramzan, Neelam
Graphical abstract: Highlights: Thermo-economic analysis of dry feed IGCC co-generation designs for lignite coal. Co-generation of methane, ammonia and electricity with CO2 capture was considered. Scenarios of flexible production and variable market prices were investigated. Flexible operation with high methane production has maximum revenue. ARS-IGCC integration caused an increase in efficiency and reduction in emissions. Abstract: Greenhouse gas emissions have become a major issue during power generation from coal due to global warming effects. Integrated gasification combined cycle (IGCC) power system has been acknowledged as a rare existing opportunity to utilize low-quality solid fuels with reduced emissions and co-generation of power, fuels and chemicals. Country like, Pakistan, where huge reserves of low-quality coal are present can benefit from this technology. In this work, the steady-state thermodynamic and economic evaluation of IGCC co-generation system has been performed for methane and ammonia production along with power generation. Gasification of coal has been simulated using entrained flow Shell gasifier under thermochemical equilibrium with the Gibbs free energy approach using local Thar lignite in Aspen Plus® V.11. The designs simulated include, IGCC 100% power with and without carbon capture, and IGCC co-generation system with carbon capture with varied production of methane, ammonia and electricity. Thermal efficiency, cost of electricity and CO2 avoided costs have been evaluated for 100% power design. Total capital in the form of total overnight cost and operating cost (fixed and variable) has been evaluated to account annualized expenditure for co-generation designs. Absorption refrigeration system (ARS) has been integrated with IGCC designs to meet the partial chilling requirement of lean solvent in Selexol process, which caused the reduction in CO2 emission because of reduced auxiliary power consumption. The net electrical efficiency of 100% power (design-2) is 32.33%, and the improved efficiency after ARS integration is 32.61%. The performance of co-generation designs is evaluated by estimating annualized revenue and annualized expenditures. One of the co-generation cases (design-4) with high methane, low ammonia and medium electricity generation, showed better performance with respect to reduced GHG emissions at almost same revenue to expenditure ratio as compared to design-2.